Crystal growth study of K-F nanozeolite and its catalytic behavior in Aldol condensation of benzaldehyde and heptanal enhanced by microwave heating - Wong, Siew Fang; Deekomwong, Krittanun; Wittayakun, Jatuporn; Ling, Tau Chuan; Muraza, Oki; Adam, Farook; Ng, Eng Poh (Elsevier, 2017)
An investigation of nanosized potassium aluminosilicate F-type zeolite (K-F, structure code EDI) converted from rice husk ash (RHA) is reported. The crystallization process was studied in an organic template-free system under microwave radiation at 100 °C and the evolution was followed by spectroscopy and microscopy techniques. The study indicated that the crystallization rate of K-F zeolite was significantly enhanced using microwave radiation. The zeolite started to nucleate at 0.5 min and flattened cuboid shaped K-F zeolite crystals (ca. 39 nm, Si/Al = 1.26) were formed after 2 min onwards. The nanocrystalline K-F zeolite exhibited good catalytic performance in solvent-free Aldol condensation reaction between benzaldehyde and heptanal, with ca. 75% reactant conversion and ca. 67% jasminaldehyde selectivity even after fifth cycle of reaction.